Will this be a record‐breaking century for human longevity?. Issue 6 (28th November 2021) - Pearce, Michael; Raftery, Adrian E.
Abstract : The record for oldest human being was set in 1997 by Jeanne Calment of France at 122 years and 164 days. Michael Pearce and Adrian E. Raftery expect that record will be broken in the coming decades Abstract : The record for oldest human being was set in 1997 by Jeanne Calment of France at 122 years and 164 days. Michael Pearce and Adrian E. Raftery expect that record will be broken in the coming decades.